Nonviolent revolutions civil resistance in the late 20th century - Nepstad, Sharon Erickson (Oxford : Oxford University Press, 2011)
In this work, Sharon Erickson Nepstad analyzes civilian insurrections in China, East Germany, Panama, Chile, Kenya, and the Philippines.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Government, Resistance to -- History -- 20th century; Revolutions -- History -- 20th century